Microstructured dextran hydrogels for burst-free sustained release of PEGylated protein drugs. (September 2015) - Bae, Ki Hyun; Lee, Fan; Xu, Keming; Keng, Choong Tat; Tan, Sue Yee; Tan, Yee Joo; Chen, Qingfeng; Kurisawa, Motoichi
Abstract: Hydrogels have gained significant attention as ideal delivery vehicles for protein drugs. However, the use of hydrogels for protein delivery has been restricted because their porous structures inevitably cause a premature leakage of encapsulated proteins. Here, we report a simple yet effective approach to regulate the protein release kinetics of hydrogels through the creation of microstructures, which serve as a reservoir, releasing their payloads in a controlled manner. Microstructured dextran hydrogels enable burst-free sustained release of PEGylated interferon over 3 months without compromising its bioactivity. These hydrogels substantially extend the circulation half-life of PEGylated interferon, allowing for less frequent dosing in a humanized mouse model of hepatitis C. The present approach opens up possibilities for the development of sustained protein delivery systems for a broad range of pharmaceutical and biomedical applications.